Acoustic Surveillance in Brazil: The Car Wash Operation Panacousticon - Leonardo Cardoso (Law Text Culture, 2020)
In Discipline and Punish, Michel Foucault famously described Jeremy Bentham’s panopticon as the emblematic representation of a shift in power from public and centralised punishment to diffuse and individualised surveillance. Within surveillance studies, Foucault’s panopticon has become a dominant analytical framework. Although Foucault considers the panopticon as a matter of optics and visibility exclusively, Bentham was not oblivious to acoustics. For instance, in his panopticon plans, he considered including a network of “sound pipes.” Compared to its visual counterpart, such a ‘panacousticon’ presents two distinctive traits. One trait is the symmetry between the inspector and inspected, as information could flow in both directions – ‘toward the scene of discovery but also toward the listener’ (Szendy 2017: 23). The other trait refers to versatility: the inspector can use the sound pipe for eavesdropping, monitoring, and as a channel for public addresses. In this article, I examine acoustic surveillance in Brazil within the context of the Car Wash Operation (Operação Lava Jato), the country’s largest corruption investigation, launched in 2014. I argue that the Operation’s success is directly related to its use of ‘sound pipes’ such as wiretaps, plea deals, and leaks. I start examining Brazil’s legal mechanisms that prohibit (silence layers) or permit (auditory probes) state interference into people’s private acoustic spheres. The second part of the article describes the Car Wash Operation was able to build and deploy its panacousticon.